The Blockchain That Was Not: The Case of Four Cooperative Agroecological Supermarkets - Rocas-Royo, Marc (Frontiers in Blockchain, 2021)
Blockchain is a technology with many applications derived from its properties. This article analyzes the case of four cooperative agroecological supermarkets and, in what circumstances, blockchain is an exciting technology to adopt. The analysis of the gathered data reveals ten factors to consider, five internal and five external. Those factors derive into six blockchain domains to develop. The article concludes that in three of them, the drawbacks of implementing the technology, although it is theoretically appropriate, are insuperable. The paper contributes to demystifying blockchain technology and applying the same business logic we use with other technical options.